Why AWD isn't taking off: Understanding barriers and pathways for scaling in gravity-fed irrigation systems in rice landscape - Evangelista, Gio Karlo; Samoy-Pascual, Kristine; Cabangon, Romeo J.; Regalado, Manuel J.; Enriquez, Yuji; Lampayan, Rubenito; Rala, Arnel; Yadav, Sudhir (Elsevier, 2025)
"CONTEXT Alternate Wetting and Drying (AWD) offers considerable potential to reduce water use and methane emissions in irrigated rice systems without compromising yields. However, despite decades of promotion, AWD adoption remains limited, especially in gravity-fed irrigation systems where institutional and agro-environmental complexities pose challenges to implementation. OBJECTIVE This study assessed the biophysical, socio-economic, and institutional determinants of AWD adoption at the turnout level in a gravity-fed irrigation system in Nueva Ecija, Philippines. The aim was to identify key barriers and opportunities for scaling AWD under spatially heterogeneous and rotationally scheduled irrigation conditions. METHODS Six turnouts within the Lateral G canal of the Upper Pampanga River Integrated Irrigation System were selected. Data were collected on plot elevation, soil texture, ownership patterns, water application, and grain yield. Water governance structures were analysed through focus group discussions and interviews with stakeholders. A decision logic framework was used to classify AWD adoption based on field-level water depth measurements. RESULTS AND CONCLUSIONS AWD reduced irrigation input by 21 % in the dry season and 50 % in the wet season while maintaining yields. However, adoption was constrained by elevation-driven water flow patterns, clay distribution, tenant-operated plots, and rigid rotational schedules. AWD adoption was more feasible during the wet season due to reduced irrigation risk. Weak farmer engagement in decision-making limited field-level adaptability. SIGNIFICANCE Scaling AWD requires reconfigured irrigation governance, integration of real-time water monitoring technologies, and economic incentives such as carbon financing. Context-specific, multi-level interventions are essential to enable large-scale AWD implementation in gravity-fed systems."